MEMBANGUN CITRA MEREK MELALUI PRODUK YANG BERKUALITAS PADA USAHA MIKRO KECIL MENENGAH (UMKM) BOJONGSARI DEPOK - Handayani, Yesie; Agustiani, Mulia; Pratama, Adi; Punisih, Punisih; Tomana, Josef; Kasmad, Kasmad; Arianto, Nurmin (Faculty of economcs Universitas Singaperbangsa Karawang, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia's economy, particularly in creating employment opportunities and improving public welfare. However, many MSMEs, including those in Bojongsari, Depok, face challenges in building a strong brand image to enhance product competitiveness. This study aims to analyze the relationship between product quality and brand image formation in MSMEs in Bojongsari and provide strategic solutions to support business sustainability. The Community Service Program (PKM) was carried out through outreach and training, covering topics such as branding, brand image, product quality, and business legality aspects. The results showed high enthusiasm from participants, with a deep understanding of the importance of brand image and product quality in enhancing competitiveness. This program proved effective in providing practical insights to support MSMEs' marketing strategies. The findings contribute significantly to strengthening the position of MSMEs in local and national markets and open opportunities for sustainable innovation in business development.